A 2D Rashba electron gas with large spin splitting in Janus structures of SnPbO2. Issue 20 (7th May 2020) - Zhang, Changcheng; Sun, Zhipeng; Lin, Yifeng; Guan, Lixiu; Tao, Junguang
Abstract : Large spin splitting induced by SOC in the Janus structure of SnPbO2 . Abstract : For realizing two-dimensional (2D) spintronic devices, controllable manipulation of different spin channels is needed. In order to achieve this goal, the materials should have well-separated spin energies induced by spin–orbit coupling (SOC). However, a negligible SOC effect in 2D SnO limits its application in this prospect. Herein, we demonstrate that the stable Janus structure of SnPbO2 can exhibit large spin splitting (67 meV) at the valence band maximum (VBM) due to the breakdown of inverse symmetry. This spin splitting is larger than the thermal fluctuation at room temperature as well as some other 2D systems. In addition, the splitting can be further enhanced by strains (82 meV) or hole doping (147 meV). More importantly, there are no other electronic states except for the Rashba states at the VBM, which make it ideal for practical applications. Our study provides alternative ways to regulate the electronic structure of SnO and the feasibility for spin manipulation in this interesting 2D system.